2018
DOI: 10.1021/acs.cgd.7b01600
|View full text |Cite
|
Sign up to set email alerts
|

Salts and Salt Cocrystals of the Antibacterial Drug Pefloxacin

Abstract: Pefloxacin (PEF) is an amphoteric, antibacterial drug which exists as a neutral molecule in the crystal structure stabilized by C–H···O and C–H···F interactions. The design of multicomponent solids using crystal engineering was undertaken in a cocrystal/salt screen of PEF with generally recognized as safe (GRAS) dicarboxylic acids to improve the solubility and phase stability of the drug. Ten multicomponent forms, namely, five salts, two salt hydrates, and three salt cocrystals, were prepared by liquid-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 49 publications
0
31
0
1
Order By: Relevance
“…[20][21][22][23][24] The electrostatic interactions in the noncovalent self-assemblies of inorganic complexes are common. [25][26][27][28] Among many examples of organic salts forming cocrystals the salts of active pharmaceutical ingredients, [25] carboxylic acid, [20][21][22][23][24] quaternary ammonium [29] and heterocycle containing oximes [30] are well studied. Depending on the reactivity of a base dicarboxylic acids form salts with different stoichiometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24] The electrostatic interactions in the noncovalent self-assemblies of inorganic complexes are common. [25][26][27][28] Among many examples of organic salts forming cocrystals the salts of active pharmaceutical ingredients, [25] carboxylic acid, [20][21][22][23][24] quaternary ammonium [29] and heterocycle containing oximes [30] are well studied. Depending on the reactivity of a base dicarboxylic acids form salts with different stoichiometries.…”
Section: Introductionmentioning
confidence: 99%
“…Charge‐assisted hydrogen bonds have definite scopes in the synthesis of non‐covalent assemblies . The electrostatic interactions in the non‐covalent self‐assemblies of inorganic complexes are common . Among many examples of organic salts forming cocrystals the salts of active pharmaceutical ingredients, carboxylic acid, quaternary ammonium and heterocycle containing oximes are well studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected to have a combined benefit of the salt and cocrystal properties, such as improved stability, solubility, dissolution, as well as enhanced the bioavailability [ 12 , 13 , 14 , 15 , 16 ]. As previously reported, salt cocrystal niclosamide and salt cocrystal pefloxacin can enhance solubility and dissolution [ 17 , 18 ]. Moreover, our previous research has shown that a salt cocrystal can be made from saccharine sodium salt with theophylline, as well as acidic saccharine with a similar excipient [ 19 ].…”
Section: Introductionmentioning
confidence: 55%
“…This study aimed to discover salt cocrystals of NDH with LP (abbreviated NDP) to obtain the drug’s superior properties, namely, stability, solubility, and dissolution [ 3 , 4 , 5 , 6 , 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Considering that ND was unstable, we initially arranged a cocrystal from NDH to develop a suitable and practical method, which can be performed readily even under the ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A shift in the vibrational frequency of the multi-component molecular crystal with respect to the individual molecular entities denotes the formation of new hydrogen bonds and other weak noncovalent forces [38][39][40]. As depicted in Figure S1, from the IR spectrum of NPG, carbonyl stretching frequencies of the carboxylic acid are observed at 1724.17 and 1415.18 cm −1 .…”
Section: Spectroscopic Analysismentioning
confidence: 97%